Case studies in co-benefits approaches to climate change mitigation and adaptation. Issue 4 (3rd April 2017) - Spencer, Benjamin; Lawler, Josh; Lowe, Celia; Thompson, LuAnne; Hinckley, Tom; Kim, Soo-Hyung; Bolton, Susan; Meschke, Scott; Olden, Julian D.; Voss, Joachim
Abstract : Attempts to mitigate greenhouse gas emissions or manage the effects of climate change traditionally focus on management or policy options that promote single outcomes (e.g., either benefiting ecosystems or human health and well-being). In contrast, co-benefits approaches to climate change mitigation and adaptation address climate change impacts on human and ecological health in tandem and on a variety of spatial and temporal scales. The article engages the concept of co-benefits through four case studies. The case studies emphasize co-benefits approaches that are accessible and tractable in countries with human populations that are particularly vulnerable to climate change impacts. They illustrate the potential of co-benefits approaches and provide a platform for further discussion of several interdependent principles relevant to the implementation of co-benefits strategies. These principles include providing incentives across multiple scales and time frames, promoting long-term integrated impact assessment, and fostering multidimensional communication networks.